2017
DOI: 10.1093/nar/gkx126
|View full text |Cite
|
Sign up to set email alerts
|

RAD51 interconnects between DNA replication, DNA repair and immunity

Abstract: RAD51, a multifunctional protein, plays a central role in DNA replication and homologous recombination repair, and is known to be involved in cancer development. We identified a novel role for RAD51 in innate immune response signaling. Defects in RAD51 lead to the accumulation of self-DNA in the cytoplasm, triggering a STING-mediated innate immune response after replication stress and DNA damage. In the absence of RAD51, the unprotected newly replicated genome is degraded by the exonuclease activity of MRE11, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 46 publications
(91 reference statements)
1
108
0
1
Order By: Relevance
“…RAD51 is the central protein in the homologous recombination (HR) pathway and is critical for DNA replication and repair. Recent studies have reported that RAD51 is also implicated in the suppression of innate immunity [46]. Hu et al pointed out that RAD51 expression was elevated by a KRAS mutation which predominantly occurred in lung adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…RAD51 is the central protein in the homologous recombination (HR) pathway and is critical for DNA replication and repair. Recent studies have reported that RAD51 is also implicated in the suppression of innate immunity [46]. Hu et al pointed out that RAD51 expression was elevated by a KRAS mutation which predominantly occurred in lung adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…A cell line derived from an ATLD patient containing an MRE11 mutation that abrogates its DNA binding properties has defects in IFN production (198). Interestingly, RAD51 absence can also induce an innate response (199). RAD51 protects DNA inside the nucleus from MRE11-mediated nucleolytic degradation.…”
Section: Mrn and The Innate Immune Responsementioning
confidence: 99%
“…The involvement of cytoplasmic DNA in AGS etiology is further highlighted by the role of the exonuclease TREX1, another gene frequently mutated in AGS patients. In line with this, depletion of RAD51 in both murine and human cell lines increases IFN signaling upon irradiating DNA damage (Bhattacharya et al, 2017). The accumulation of ssDNA in the absence of TREX1 leads to an exhaustion of RAD51 and RPA, which in turn directly contributes to the generation of replication stress and p53-dependent checkpoint signaling in addition to the activation of a cGAS-STING-mediated IFN response (Fig 5B).…”
Section: Compromised Rer Causes Aicardi-goutières Syndromementioning
confidence: 54%
“…The accumulation of ssDNA in the absence of TREX1 leads to an exhaustion of RAD51 and RPA, which in turn directly contributes to the generation of replication stress and p53-dependent checkpoint signaling in addition to the activation of a cGAS-STING-mediated IFN response ( Fig 5B). In line with this, depletion of RAD51 in both murine and human cell lines increases IFN signaling upon irradiating DNA damage (Bhattacharya et al, 2017). This suggests that the release of self-derived DNA into the cytoplasm is a general phenomenon during DNA replication stress and is counteracted by mechanisms acting both at the stalled replication fork and in the cytoplasm.…”
Section: Compromised Rer Causes Aicardi-goutières Syndromementioning
confidence: 63%